A comparative evaluation of fracture resistance of endodontically treated teeth using different post-obturation restorative materials: An In Vitro study - Simran Chawla; Tarun Kumar; Sunandan Mittal; Vanita Keshav; Vidushi Gilhotra; Prabhprit Kaur (Wolters Kluwer Medknow Publications, 2024)
This in vitro study was conducted to evaluate and compare the fracture resistance of endodontically treated teeth using different post-obturation restorative materials. Seventy-five non-carious extracted human teeth were collected. Access opening, chemicomechanical preparation, and obturation were done. Teeth were randomly divided into various groups depending on the type of post-endodontic restoration: group I-control group, group II-Tetric-N-Flow Bulk Fill, group III-Tetric-N-Flow Bulk Fill + everX Posterior, group IV-P60, and group V-P60 + everX Posterior. The fracture resistance of each sample was measured using the universal testing machine. Results: The results obtained were subjected to statistical analysis. This demonstrated that group III (Tetric-N-Flow Bulk Fill + everX Posterior) was shown to be the most effective group followed by group V (Filtek P60 + everX Posterior) out of all of the other restorative experimental groups. Conclusion: Tetric-N-Flow Bulk Fill + everX Posterior showed maximum fracture resistance among the experimental groups.